Looking for needles in a haystack: Key issues affecting children's rights in the General Data Protection Regulation. Issue 2 (April 2018) - Lievens, Eva; Verdoodt, Valerie
Abstract: The EU General Data Protection Regulation (GDPR) devotes particular attention to the protection of personal data of children. The rationale is that children are less aware of the risks and the potential consequences of the processing of their personal data on their rights. Yet, the text of the GDPR offers little clarity as to the actual implementation and impact of a number of provisions that may significantly affect children and their rights, leading to legal uncertainty for data controllers, parents and children. This uncertainty relates for instance to the age of consent for processing children's data in relation to information society services, the technical requirements regarding parental consent in that regard, the interpretation of the extent to which profiling of children is allowed and the level of transparency that is required vis-à-vis children. This article aims to identify a number of key issues and questions – both theoretical and practical – that raise concerns from a multi-dimensional children's rights perspective, and to clarify remaining ambiguities in the run-up to the actual application of the GDPR from 25 May 2018 onwards.